2017
DOI: 10.1016/j.burns.2017.10.001
|View full text |Cite
|
Sign up to set email alerts
|

The impact of operative time and hypothermia in acute burn surgery

Abstract: Patients who undergo prolonged surgeries and become hypothermic are more likely to develop complications. We therefore advocate for diligent adherence to strategies to prevent hypothermia and recommend limiting operative time in clinical circumstances where intraoperative measures are unlikely to adequately prevent hypothermia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(18 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“… 53 , 54 Specifically, hypercapnia, anemia, and hypothermia all contribute to diminished autoregulation and are exacerbated by prolonged surgery. 53 , 55 , 56 Surgical duration is affected by many factors, including the complexity of the injury, the difficulty of the procedure, and the technical expertise of the surgical team. This lends further support to the notion that hip fractures should ideally be managed expeditiously, by experienced surgeons and anesthetists who are able to complete the surgery safely and quickly.…”
Section: Discussionmentioning
confidence: 99%
“… 53 , 54 Specifically, hypercapnia, anemia, and hypothermia all contribute to diminished autoregulation and are exacerbated by prolonged surgery. 53 , 55 , 56 Surgical duration is affected by many factors, including the complexity of the injury, the difficulty of the procedure, and the technical expertise of the surgical team. This lends further support to the notion that hip fractures should ideally be managed expeditiously, by experienced surgeons and anesthetists who are able to complete the surgery safely and quickly.…”
Section: Discussionmentioning
confidence: 99%
“…We included burn injuries of different degrees and stratified based on age, that were treated in both inpatient and outpatient settings. Albeit the %TBSA was not specified in the ACS-NSQIP database, a large body of evidence indicates that the vast majority of our patient cohort suffered minor burns with <10% TBSA: Namely, (i) the average operation time of less than one hour, (ii) the comparatively low mortality and morbidity, (iii) the relatively short LOS, and (iv) the nearly equal number of in-and outpatient care support the hypothesis of predominantly minor burn injuries (8,15,(22)(23)(24)(25)(26).…”
Section: Discussionmentioning
confidence: 69%
“…Disruption of cerebral autoregulation might also occur during surgery [ 39 , 40 ]. In particular, hypercapnia, anaemia, and hypothermia all affect autoregulation and can be exacerbated by a prolonged surgery [ 41 , 42 ]. Furthermore, previous studies reported that in the case of surgery for cardiac disease, a prolonged surgical duration was associated with an impaired cognitive function [ 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%